Case-srufy: East Asia in World Political and Economic Processes - Kseniia Aleksandrovna Efremova; Dmitrii Viktorovich Strel'tsov (Сравнительная политика)
The purpose of the section is to analyze the latest developments in the military and political sphere in East Asia, taking into account a wide range of challenges. The authors also analyze the role of regional organizations, processes of regionalization and regionalism in East Asia, as well as the development of interregional relations of various association and key countries of the region.